Retrospective analysis of the occurrence, potential risk factors and medical significance of pulmonary complications after total shoulder arthroplasty from the National Inpatient Sample database (2010–2019) - Mengning Dong; Huitong Liang; Jinlang Fu; Zeying Guo; Hao Xie; Qinfeng Yang; Qingmei Yu; Xiaomin Hou (Perioperative Medicine)
Abstract Background In USA, total shoulder arthroplasty (TSA) ranks amongst the top five surgeries that require hospitalization. As a result, the healthcare system in USA could face a considerable financial strain due to the emergence of subsequent pulmonary problems. This study aimed to conduct a thorough examination of the prevalence, influential factors and medical importance of pulmonary complications, with emphasis on pneumonia, respiratory failure and pulmonary embolism (PE) following total shoulder arthroplasty (TSA) procedures in USA. Methods The National Inpatient Sample (NIS) was utilized to survey all patients who underwent primary elective TSA from 2010 to 2019. Pneumonia, respiratory failure and PE following TSA were considered to be pulmonary consequences. The inpatient expenses, length of hospitalization, death rates and patient characteristics of those with and without reported perioperative pulmonary problems were compared. The utilization of trend weights was necessary to obtain incidence estimates across USA, considering the stratified framework of the NIS database and the dependence on observed frequencies within the database. Two assessments were utilized to assess the projected annual rates of complications. Results Between 2010 and 2019, a total of 189,695 patients were estimated to underwent primary elective TSA. Infections, such as pneumonia, respiratory failure or PE, complicated 1.4% (95% CI, 1.52%–1.64%) of TSA operations. The ailments at this period that were most likely to result in pulmonary problems were ulcer (adjusted odds ratio [AOR] = 9.43; 95% CI, 4.99–46.91), pulmonary circulation disorders (AOR = 9.01; 95% CI, 4.56– 31.92), weight loss (AOR = 4.84; 95% CI, 2.15–10.88), fluid and electrolyte disorders (AOR = 3.55; 95% CI, 2.55–4.95), alcohol abuse (AOR = 1.56; 95% CI, 1.08–2.26), congestive heart failure (AOR = 3.09; 95% CI, 1.83–5.24), chronic pulmonary disease (AOR = 2.45; 95% CI, 1.60–3.75), deficiency anaemia (AOR = 1.56; 95% CI, 1.08–2.26), depression (AOR = 1.47; 95% CI, 1.03–2.11) and obesity (AOR = 1.46; 95% CI, 1.01–2.11). A correlation was found between perioperative pulmonary problems and extended LOS (+ 3 days; 95% CI, 2–6) and increased hospitalization costs (= + 20,514 US dollars; 95% CI, 14,109–35,281). Conclusions This investigation primarily aimed to ascertain potential risk factors linked to pulmonary issues that may occur after TSA. The analysis revealed that the pneumonia rates decreased each year, whereas the PE rates remained relatively stable. A noticeable and consistent increase was found in respiratory failure from 2010 to 2019. The findings suggests that individuals who are older (primarily between the ages of 60 and 80 years) and female exhibit increased rates. These factors could help stratify patients and reduce the risk of potential complications. This claim is especially applicable in PE because it is associated with more significant improvements in resource utilization.